Food Safety Knowledge and Practice in the Era of Dark Kitchens - Chitika Pudaruth; Susheela Biranjia-Hurdoyal (BioMed Target Journal)
Online ordering and food product sales are well-tolerated in many countries. Post-COVID-19, the business of online food purchases has soared, and many home-based suppliers (dark kitchens) have become part of this endeavor. This practice could impact the quality and safety of the food products with the risk of adverse effects on human health arising from food-borne illnesses and spoilage. The knowledge and practice of a random sample of Mauritians on the quality and safety of locally produced processed food items was investigated. Factors that could influence the purchase of dark kitchens were also studied. Data was collected from 258 participants through a survey questionnaire in March 2022. Up to 99.2 % reported that food suppliers should adhere to hazard analysis critical control points and international standard operation to guarantee quality. The study indicated that 45% of the respondents purchased from dark kitchens. Inadequate scores for both knowledge and practice were noted. The correlation between knowledge and practice was moderate (τ = 0.088; p = 0.00). Furthermore, it was observed that dark kitchen' purchases were motivated by easy accessibility, food quality, and low prices. Food labels were reported as an important characteristic of food products in general. However, in practice, only 31% reported labels and 27.1% reported the site of preparation as an important factor when they decide on the site of purchase.  The participants were aware of hygienic practices, the impact of unsafe food on their health and the importance of food standards. Yet, purchases from unchecked sources remain prominent. By fostering awareness and understanding, behavioral changes among individuals could be investigated, contributing to an overall improvement in public health and preventing food-related illnesses.